The Effectiveness Of The Training Courses And Lessons For The New Owners In Developing Their Teaching Skills From Their Point Of View (Journal of the College of Basic Education, 2024)
The research aims to find out (the extent of the effectiveness of the training courses and lessons for the new staff in developing their teaching skills from their point of view), and to achieve what the research aimed to achieve, the researcher followed the descriptive approach and the research community is represented by the new staff (teachers - teachers) in the Mansouriya District (who number (862)) His sample consisted of (200)Teacher and teacher. The research tool was a questionnaire prepared by the researcher after reviewing previous studies. The questionnaire, in its final form, consisted of (40) items after ensuring its validity and reliability. It was applied to the sample members who participated in the training courses and lessons, and the researcher used the Statistical Package for the Social Sciences (SPSS-26) program. To treat the data statistically, the results showed that the total score of the questionnaire was statistically significant at a level of significance (0.05), a degree of freedom (73), and a tabular t-value (2.000), meaning that its arithmetic mean was greater than the hypothesized arithmetic mean. Likewise, the five areas of the questionnaire were statistically significant, and the results also showed that The paragraphs are all functional Statistically, with the exception of four items, they were not statistically significant in favor of the hypothesized arithmetic mean. This indicates the effectiveness of the training courses and lessons for the new staff in developing their teaching skills from their point of view after addressing the matters that I mentioned before them. The researcher recommended several recommendations, including: Building training programs and courses in light of The needs of teaching staff and in light of their annual evaluation, the use of modern technologies in training with an emphasis on practical training, the necessity of choosing the appropriate time and place for the trainees so that it does not conflict with school hours.In continuation of the research, the researcher suggested that education directorates conduct various training programs for a specific period of time to train all teaching staff and inform them of what is new in the field of specialization.